Sonochemical-assisted green synthesis of wurtzite ZnO/ε-Zn(OH)2 (W- ZnO/ε-Zn(OH)2) nanoflakes using Calotropis gigantea leaves for effective photodegradation against methyl orange and supercapacitor application - Mahwish Bashir; Hafsa Mubeen; Asadullah; Mohd Saleh Al Ansari; Mirjalol Ismoilov; Tariq Mehmood; Mohammed Rafi Shaik; Mufsir Kuniyil; Mohammed Rafiq H. Siddiqui; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrative reverse vaccinology and computational modeling for the rational design of a broadly immunogenic multi-epitope vaccine against Marburg virus infection - Asadullah Khan; Sitara Bibi; Li Pinyi; Khalida Latif; Muhammad Rahiyab; Ishaq Khan; Arshad Iqbal; Itazaz Ul Haq; Syed Shujait Ali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dynamic interaction of lorentz forces and arrhenius thermal kinetics in shear-thinning/thickening fluids through porous medium - S. Bilal; Asadullah; Muhammad Yasir (Dynamics of Atmospheres and Oceans, 2026)

Microbial desulfurization of low-grade Balochistan coal using Bacillus licheniformis and Bacillus pumilus - Asif Naeem; Maqsood Ahmed; Asadullah; Jamal Khan; Zahid Naeem Qaisrani (Biodegradation, 2026)

Hydro-geochemical Assessment of Groundwater in a Semi-Arid Region of Western Afghanistan (Herat) Using the Entropy Water Quality Index (EWQI) and Multivariate Analysis - Asadullah Farahmand; Hussain Ali Jawadi; Abdulhalim Zaryab; Shakir Ali; Mohammad Salem Hussaini; Manuel Abrunhosa; Fayezurahman Azizi (Water Conservation Science and Engineering, 2025)

Physicochemical investigation of groundwater within the confinement of Sargodha city and remediation pathways for contaminants - Irum Fatima; Asadullah Dawood; Abdul Muneeb Khan; Sumayya Kanwal; Zainab Bibi; Akbar Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Metal organic frameworks (MOFs) synthesis and their use as a loading agent in oxidative stress-based diseases - Muhammad Saqib Saif; Sana Batool; Yusra Majeed; Asadullah; Tuba Tariq; Li Haitao; Yanjun Duan; Ghazala Mustafa; Murtaza Hasan (Journal of Environmental Chemical Engineering, 2025)

Evaluating chromite ore deposits: An integrated magnetic and geochemical study in the Kohistan Island Arc of northern Pakistan - Syed Tallataf Hussain Shah; Arsalan Iftikhar; Syed Mohib Ali; Umair Inayat; Asadullah Khan; Faizan Ur Rehman Qaiser; Javed Iqbal Tanoli (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Evaluation of groundwater quality of Mirpurkhas District, Sindh, Pakistan, for drinking, irrigation and multivariate analysis - Asadullah Khaskheli; Taj Muhammad Jahangir Khuhawar; Muhammad Yar Khuhawar; Faheem Yar Khuhawar; Muhammad Farooque Lanjwani; Abdul Qayoom Landar (Arabian Journal of Geosciences, 2025)

First record of Acentrogobius dayi Koumans 1941 (Teleostei: Gobiidae) on the Balochistan Coast, Northern Arabian Sea - Asadullah Ali Muhammad; Ateeqa Baloch; Sumera Farooq; Imtiaz Kashani (Thalassas: An International Journal of Marine Sciences, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Length-Based Fishery Status of Indian White Prawn (Penaeus Indicus, Milne-Edwards, 1837) in the Northern Waters of the Oman Sea (Iran) - Seyed Ahmadreza Hashemi; Mastooreh Doustdar; Parastoo Mohebi Derakhsh; Asadullah Ali Muhammad (Thalassas: An International Journal of Marine Sciences, 2024)

Identification and characterization of functional microRNAs and their significant targets in maize plants - Abdul Baqi; Samiullah; Ghulam Mustafa Khan; Asadullah; Naqeebullah Khan; Attiq-Ur-Rehman; Alia Ahmed (Journal of Plant Biochemistry and Biotechnology, 2024)

Eco-tech fusion: Unraveling the nonparametric causal effects of fintech, natural resources, digital infrastructure, and economic growth on environmental sustainability from a quantile perspective - Mansoora Ahmed; Asadullah Khaskheli; Syed Ali Raza; M. Kabir Hassan (Resources Policy, 2024)

Utilization of macadamia nutshell-derived activated carbon for enhanced congo red adsorption - Asadullah; Kittaporn Ngiwngam; Pornchai Rachtanapun; Gopinath Kasi; Jaejoon Han; Wirongrong Tongdeesoontorn (Bioresource Technology Reports, 2024)

Evaluating groundwater storage variations in Afghanistan using GRACE, GLDAS, and in-situ measurements - Hussain Ali Jawadi; Asadullah Farahmand; Roderick Fensham; Nilanchal Patel (Modeling Earth Systems and Environment, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Application of machine learning and multivariate approaches for assessing microplastic pollution and its associated risks in the urban outdoor environment of Bangladesh - Tapos Kumar Chakraborty; Md. Sozibur Rahman; Md. Simoon Nice; Baytune Nahar Netema; Khandakar Rashedul Islam; Partha Chandra Debnath; Pragga Chowdhury; Monishanker Halder; Samina Zaman; Gopal Chandra Ghosh; Md Abu Rayhan; Sk Mahmudul Hasan Asif; et al. (Journal of Hazardous Materials, 2024)

Old drug, new tricks: polymer-based nanoscale systems for effective cytarabine delivery - Nasrullah Jan; Hassan Shah; Safiullah Khan; Faiza Nasar; Asadullah Madni; Syed Faisal Badshah; Ahsan Ali; Mohammad F. Bostanudin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Geochemical evolution of spring waters in carbonate dominated aquifer in Upper Shirin Tagab sub-basin, northern Afghanistan - Abdulhalim Zaryab; Asadullah Farahmand; Zamen Jafari; Shakir Ali; Farshad Alijani; Hamid Reza Nassery (Groundwater for Sustainable Development, 2024)

Retraction Note: Natural Polymer–Based Graphene Oxide Bio-nanocomposite Hydrogel Beads: Superstructures with Advanced Potentials for Drug Delivery - Sadia Rehman; Asadullah Madni; Qazi Adnan Jameel; Faisal Usman; M. Rafi Raza; Faiz Ahmad; Hina Shoukat; Hamdan Aali; Afifa Shafiq (AAPS PharmSciTech, 2024)

Biological Factors Changes in the Persian Gulf after 19 Years (In the Cold Period) - Mahnaz Rabbaniha; Arash Haghshenas; Farahnaz Kian Arsi; Fereidoon Owfi; Fereshteh Seraji; Asadullah Ali Muhammad; Sumera Farooq (Thalassas: An International Journal of Marine Sciences, 2024)

Sustainable adsorption of methylene blue onto biochar-based adsorbents derived from oil palm empty fruit branch: Performance and reusability analysis - Kanogwan Tohdee; Surat Semmad; Apiniti Jotisankasa; Bunjerd Jongsomjit; Thotsaporn Somsiripan; Asadullah (Bioresource Technology Reports, 2024)

Development and Statistical Optimization of Polymer-Based Nanoparticulate Delivery System for Enhancing Cytarabine Efficacy in Leukemia Treatment - Nasrullah Jan; Asadullah Madni; Hassan Shah; Safiullah Khan; Qazi Amir Ijaz; Syed Faisal Badshah; Ahsan Ali; Umair Khurshid; Mohammad F. Bostanudin (Journal of Pharmaceutical Innovation, 2023)

Hydrogeochemical and isotopic evolution of groundwater in shallow and deep aquifers of the Kabul Plain, Afghanistan - Abdulhalim Zaryab; Asadullah Farahmand; Hamid Reza Nassery; Farshad Alijani; Shakir Ali; Mohammad Zia Jamal (Environmental Geochemistry and Health, 2023)

Identification and apportionment of groundwater nitrate sources in Chakari Plain (Afghanistan) - Abdulhalim Zaryab; Asadullah Farahmand; Thomas J. Mack (Environmental Geochemistry and Health, 2023)

Assessment of the phycosphere microbial dynamics of microbial community associated with red algae culture under different cultural conditions - Asadullah Gujar; Muhammmad Ahsan Asghar; Muneefah Abdullah Alenezi; Muhammad Saleem Kubar; Kashif Ali Kubar; Ali Raza; Khansa Saleem; Hafiz Hassan Javed; Abu Zar Ghafoor; Muhammad Iftikhar Hussain; Abd Ullah; Hongli Cui; et al. (Environment, Development and Sustainability, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Carbohydrate-coated nanoparticles for PCR-less genomic detection of Salmonella from fresh produce - Saad Asadullah Sharief; Oznur Caliskan-Aydogan; Evangelyn C. Alocilja (Food Control, 2023)

Correction: Comparative studies of enhancing oil recovery optimization for optimum oil feld development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Azizullah Shaikh; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

Comparative studies of enhancing oil recovery optimization for optimum oil field development - Muhammad Usman Tahir; Hongtao Zhou; Bilal Shams Memon; Wei David Liu; Asadullah Memon; Danish Khan; Allah Bakhsh (Modeling Earth Systems and Environment, 2023)

The asymmetric relationship between public–private partnerships investment in energy and environmental degradation for sustainable development: new evidence from quantile-on-quantile regression approach - Sun Guoyan; Asadullah Khaskheli; Syed Ali Raza; Sajid Ali (Environmental Science and Pollution Research, 2023)

A review on pillared clay-based catalysts for low-temperature selective catalytic reduction of NO with hydrocarbons - Muhammad Kashif; Minhao Yuan; Yaxin Su; Philippe M. Heynderickx; Asadullah Memon (Applied Clay Science, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Impact of tourism development upon environmental sustainability: a suggested framework for sustainable ecotourism - Qadar Bakhsh Baloch; Syed Naseeb Shah; Nadeem Iqbal; Muhammad Sheeraz; Muhammad Asadullah; Sourath Mahar; Asia Umar Khan (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Natural Polymer-Based Graphene Oxide Bio-nanocomposite Hydrogel Beads: Superstructures with Advanced Potentials for Drug Delivery - Sadia Rehman; Asadullah Madni; Qazi Adnan Jameel; Faisal Usman; M. Rafi Raza; Faiz Ahmad; Hina Shoukat; Hamdan Aali; Afifa Shafiq (AAPS PharmSciTech, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Assessment of groundwater vulnerability in an urban area: a comparative study based on DRASTIC, EBF, and LR models - Alimahdi Mohammaddost; Zargham Mohammadi; Mohsen Rezaei; Hamid Reza Pourghasemi; Asadullah Farahmand (Environmental Science and Pollution Research, 2022)

pH-Sensitive Nanoparticles Developed and Optimized Using Factorial Design for Oral Delivery of Gliclazide - Raida Al-Kassas; Asadullah Madni; Christina Buchanan; Andrew N. Shelling (Journal of Pharmaceutical Innovation, 2022)

Nitrate contamination in groundwater of Kabul Province, Afghanistan: Reasons behind and conceptual management framework discourse - Hussain Ali Jawadi; Mohammad Wasim Iqbal; Mohammad Naseri; Asadullah Farahmand; Abdul Haseeb Azizi; Mohammad Naiem Eqrar (Journal of Mountain Science, 2022)

Correction to: Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2022)

Quantitative models and controlling factors of Langmuir volume and pressure for the measurement of shale gas adsorption: An Analytical study based review - Asadullah Memon; Bilal Shams Memon; Temoor Muther; Abdul Sami Qureshi; Umaid Ali Uqaili; Sunder Sham Jeswani; Zaheer Hussain Zardari (Arabian Journal of Geosciences, 2022)

Nanocrystals: Characterization Overview, Applications in Drug Delivery, and Their Toxicity Concerns - Mohammed Asadullah Jahangir; Syed Sarim Imam; Abdul Muheem; Ananda Chettupalli; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Imran Kazmi; Muhammad Afzal; Sultan Alshehri (Journal of Pharmaceutical Innovation, 2022)

Nonlinear impact of municipal solid waste recycling and energy efficiency on environmental performance and economic growth: evidence from non-parametric causality-in-quantiles - Sun Guoyan; Asadullah Khaskheli; Syed Ali Raza; Maiyra Ahmed (Environmental Science and Pollution Research, 2022)

Analyzing the association between the foreign direct investment and carbon emissions in MENA countries: a pathway to sustainable development - Sun Guoyan; Asadullah Khaskheli; Syed Ali Raza; Nida Shah (Environment, Development and Sustainability, 2022)

Fruit bagging of custard apple (Annona reticulata) as an eco-friendly protection approach against mealybug (Phenacoccus solenopsis) infestation in the north-eastern Bangladesh - Tareq Ahmed; Md. Mehedi Hasan; Kamrul Hassan; Jaher D. Ahmed; Karzan Sabah D. Ahmed; Asadullah Azam; Md. Fuad Mondal (International Journal of Tropical Insect Science, 2022)

Site selection for managed aquifer recharge in the city of Kabul, Afghanistan, using a multi-criteria decision analysis and geographic information system - Mohammad Salem Hussaini; Asadullah Farahmand; Sangam Shrestha; Sanjiv Neupane; Manuel Abrunhosa (Hydrogeology Journal, 2022)
While the success and sustainability of managed aquifer recharge (MAR) strongly depends on many characteristics of the site, it is necessary to integrate the site characteristics and develop suitability maps to indicate the most suitable locations. The objective of this study is to integrate geographic information system (GIS) and multi-criteria decision analysis (MCDA) techniques to identify the most suitable areas for a MAR project in the Kabul city area, Afghanistan. Data for six effective criteria, including slope, drainage density, surface infiltration rate, unsaturated zone thickness, soil type and electrical conductivity, were collected and then a classification map was produced for each criterion in the GIS environment. By applying MCDA techniques, the weights of the effective criteria were obtained. A suitability map was generated from each technique separately based on a combination of all criteria weights and thematic layers. The result of the analytical network process (ANP) method was found to be more precise and reliable compared with that of the analytical hierarchy process (AHP) method. Based on the final suitability map produced from the ANP model, there is 3.7, 15.0, 37.4, 33.1 and 10.3% of the total area that is unsuitable, of low suitability, moderately suitable, suitable and very suitable for MAR application, respectively. As a final result of this work, seven sites have been prioritized based on land use. The integration of multi-criteria decision analysis and GIS is recognized as an effective method for the selection of managed aquifer recharge sites.

Nano-suspension combined effect with polymer gels for enhanced oil recovery in low permeability reservoir - Imran Akbar; Hongtao Zhou; Wei Liu; Abdul Sami Qureshi; Asadullah Memon; Temoor Muther; Ubedullah Ansari; Muhammad UsmanTahir; Allah Bakhsh; Azizullah Shaikh; Habibou Hamed Hamed (Arabian Journal of Geosciences, 2021)

Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2021)

Evaluation of Hydrogeoethics approach for sustainable management of groundwater resources in the upper Kabul sub-basin, Afghanistan - Asadullah Farahmand; Mohammad Salem Hussaini; Abdulhalim Zaryab; Sayed Waliullah Aqili (Sustainable Water Resources Management, 2021)

Financial development, international trade, and environmental degradation: a nonlinear threshold model based on panel smooth transition regression - Asadullah Khaskheli; Yushi Jiang; Syed Ali Raza; Komal Akram Khan; Muhammad Asif Qureshi (Environmental Science and Pollution Research, 2021)

Threshold non-linear relationship between globalization, renewable energy consumption, and environmental degradation: evidence from smooth transition models - Yushi Jiang; Asadullah Khaskheli; Syed Ali Raza; Muhammad Asif Qureshi; Maiyra Ahmed (Environmental Science and Pollution Research, 2021)

Gas Adsorption and Controlling Factors of Shale: Review, Application, Comparison and Challenges - Asadullah Memon; Aifen Li; Bilal Shams Memon; Temoor Muther; Wencheng Han; Muhammad Kashif; Muhammad Usman Tahir; Imran Akbar (Natural Resources Research, 2021)

Drought monitoring based on Standardized Precipitation Index and Standardized Precipitation Evapotranspiration Index in the arid zone of Balochistan province, Pakistan - Zahid Naeem Qaisrani; Narissara Nuthammachot; Kuaanan Techato; Asadullah (Arabian Journal of Geosciences, 2021)

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Assessment of groundwater potential through vertical electrical sounding at Haji Rehmatullah Palari village, Nooriabad - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf; Asfand Yar Wali Arain (Acta Geophysica, 2019)

Groundwater investigation through vertical electrical sounding at hilly area from Nooriabad toward Karachi - Asadullah Soomro; Abdul Latif Qureshi; Muhammad Afzal Jamali; Arshad Ashraf (Acta Geophysica, 2019)

Enhancement of Dissolution and Skin Permeability of Pentazocine by Proniosomes and Niosomal Gel - Asadullah Madni; Muhammad Abdur Rahim; Muhammad Ahmad Mahmood; Abdul Jabar; Mubashar Rehman; Hassan Shah; Arshad Khan; Nayab Tahir; Aamna Shah (AAPS PharmSciTech, 2018)

Development of Eudragit RS 100 Microparticles Loaded with Ropinirole: Optimization and In Vitro Evaluation Studies - Prince Muhammad Kashif; Asadullah Madni; Muhammad Ashfaq; Mubashar Rehman; Muhammad Ahmad Mahmood; Muhammad Imran Khan; Nayab Tahir (AAPS PharmSciTech, 2017)

Ultrasonic Processing Technique as a Green Preparation Approach for Diacerein-Loaded Niosomes - Muhammad Imran Khan; Asadullah Madni; Jouni Hirvonen; Leena Peltonen (AAPS PharmSciTech, 2017)

Effect of granulovirus infection of Spodoptera litura (Lepidoptera: Noctuidae) larvae on development of the endoparasitoid Chelonus inanitus (Hymenoptera: Braconidae) - Asadullah Azam; Yasuhisa Kunimi; Maki N. Inoue; Madoka Nakai (Applied Entomology and Zoology, 2016)

A review of the assessment and mitigation of floods in Sindh, Pakistan - Asadullah Kazi (Natural Hazards, 2014)